Hybrid lineages of CD4+ T cells: a handbook update - Bensussen, Antonio; Torres-Magallanes, José Antonio; Álvarez-Buylla, Elena R.; de Álvarez-Buylla, Elena Roces (Frontiers in Immunology, 2024)
CD4+ T lymphocytes have been classified into several lineages, according to their gene expression profiles and their effector responses. Interestingly, recent evidence is showing that many lineages could yield hybrid phenotypes with unique properties and functions. It has been reported that such hybrid lineages might underlie pathologies or may function as effector cells with protection capacities against molecular threats. In this work, we reviewed the characteristics of the hybrid lineages reported in the literature, in order to identify the expression profiles that characterize them and the markers that could be used to identify them. We also review the differentiation cues that elicit their hybrid origin and what is known about their physiological roles.